2021
DOI: 10.3928/1081597x-20201013-04
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Refractive Outcomes With the Eyecryl Phakic Toric IOL Versus the Visian Toric Implantable Collamer Lens: Results of a 2-Year Prospective Comparative Study

Abstract: PURPOSE: To compare the 2-year visual and refractive outcomes with the Eyecryl Phakic Toric IOL (EP TIOL) (Biotech Vision Care Pvt Ltd) and Visian Toric ICL (TICL) (STAAR Surgical) for correction of high myopic astigmatism. METHODS: This prospective, interventional, non-randomized comparison study included eligible patients who underwent toric phakic IOL surgery in one or both eyes with either the EP TIOL or TICL for myopic astigmatism. Two years postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
1
16
1
3
Order By: Relevance
“…2 In addition, there were sporadic reports of TICL realignment. 2,[6][7][8][9][10][11] This study confirms that the incidence of ICL realignment or exchange is low, thus suggesting that the ICL has a favorable safety profile.…”
Section: Discussionsupporting
confidence: 70%
“…2 In addition, there were sporadic reports of TICL realignment. 2,[6][7][8][9][10][11] This study confirms that the incidence of ICL realignment or exchange is low, thus suggesting that the ICL has a favorable safety profile.…”
Section: Discussionsupporting
confidence: 70%
“…Newer Toric ICL models with a central port (V4c and V5) to increase aqueous flow have been shown to decrease postoperative angle closure glaucoma. 19 Significant anterior chamber angle narrowing has been noted in other studies, 20,21 though patients in the present study did not undergo postoperative UBM to correlate anterior chamber angle changes with IOP. Other possible complications include pigment dispersion, 15 uveitis with cystoid macular edema, 15 toxic anterior segment syndrome, 13 and endophthalmitis, 13,22 none of which were seen in our study.…”
Section: Discussionmentioning
confidence: 48%
“…9 It is reported in the study that there was no significant difference between the mean UDVA, CDVA, and SE between the 2 groups at 2 years of follow-up. 9 Brar et al observed a UDVA of 20/20 or better in 76% of eyes in the Eyecryl toric pIOL group and 72% of eyes in the toric ICL group. 9 Ninety-two percent of eyes in the Eyecryl toric pIOL group and 88% of eyes in the toric ICL group were within ±0.50 D of SE.…”
Section: Discussionmentioning
confidence: 74%
“…Although a limited number of previous studies have reported the refractive predictability and safety of the Eyecryl PC pIOL, the mean follow-up in the longest series was 3 years. [9][10][11][12][13][14][15] The goal of the study was to assess the long-term efficacy and safety of Eyecryl posterior chamber spherical pIOL implantation in individuals with high myopia.…”
mentioning
confidence: 99%